2020
DOI: 10.1097/pgp.0000000000000712
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Synchronous Malignant and Benign Granular Cell Tumor of the Vulva

Abstract: Granular cell tumors (GCT) are rare soft tissue neoplasms, which seldom occur in the vulva. They are more commonly benign, but malignant GCT do occur. We report a case of a 50-yr-old postmenopausal woman who presented with a vulvar lesion that was diagnosed as GCT on biopsy. Imaging and clinical examination revealed an enlarged, likely positive lymph node. Pathology of the subsequently resected total deep vulvectomy specimen showed 2 histologically distinct GCTs. The larger lesion met criteria for malignancy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Three studies [ 7 , 14 , 26 ] reported 2 cases of malignant as well as 1 synchronous malignant and benign GCT of the vulva were identified. Firstly, Ramos et al [ 7 ] reported a 17 years patient with malignant GCT of the left labia majus, of whom were treated with left hemivulvectomy and left groin lymph node dissection soon after local resection, which involved positive surgical resection margin.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies [ 7 , 14 , 26 ] reported 2 cases of malignant as well as 1 synchronous malignant and benign GCT of the vulva were identified. Firstly, Ramos et al [ 7 ] reported a 17 years patient with malignant GCT of the left labia majus, of whom were treated with left hemivulvectomy and left groin lymph node dissection soon after local resection, which involved positive surgical resection margin.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the patient reported pulmonary, hepatic and skeletal metastases and died of hepatic failure 4 months after demission. Interestingly, Baranova et al [ 26 ] presented a 50 years old postmenopausal patient with 7 × 4 cm tumor in the left labia and partially the left mons pubis. The patient initially underwent biopsy firstly and the histological results demonstrated an infiltrative lesion with positive for S100 protein immunohistochemically.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations